Kaposi's varicelliform eruption: A case series - Bruno Ferrari; Vanina Taliercio; Paula Luna; María Eugenia Abad; Margarita Larralde (Wolters Kluwer Medknow Publications, 2015)
Kaposi's varicelliform eruption is a rare and potentially fatal viral infection caused mainly by reactivation of herpes simplex virus. It concomitantly occurs with pre-existing skin conditions, mostly atopic dermatitis, so it is predominately found in children. We present a case series that includes four adults, familial cases, and previously healthy patients. We also highlight clinical features, associations and therapeutic options.